Dinamika Hukum Islam Dan Status Sosial (Isu Keabsahan Anak Hasil Kawin Hamil Dari Berbagai Pendekatan) - Gafur, Abdul; , M.Hum, Prof. Dr. H. Jalaluddin; Azhari, M.H.I, Prof. Dr. H. Fathurahman; Hamdi, Lc, M.A, Dr. H. Fahmi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This study aims to analyze the dynamics of Islamic law and social status concerning the legitimacy of children born from premarital pregnancies from various approaches, including the perspectives of the Shafi'i School, the Marriage Law (UUP), and the Compilation of Islamic Law (KHI). The method used is qualitative with a descriptive-analytical approach, through literature studies of classical and contemporary Islamic legal sources, as well as relevant Indonesian legislation. The analysis was conducted to identify and compare the views of various legal authorities on the legal status and rights of children born from the marriages of pregnant women.The results show that according to the Shafi'i School, a child born less than six months after a legitimate marriage or in the possibility of intercourse is considered illegitimate and not attributed to the father, thus impacting the child's rights. However, if the child is born more than six months after a legitimate marriage, the child is considered legitimate and has rights to both parents.According to UUP and KHI, a child born from the marriage of a woman pregnant due to adultery is considered legitimate as long as the child is born from a legitimate marriage, thus having rights that must be fulfilled by both parents. However, if the child is born due to adultery outside a legitimate marriage, the child only has civil relations with the mother. A judicial review of Article 43 (1) UUPA resulted in a ruling that a child born out of wedlock also has civil relations with the biological father and the father's family, besides with the mother and the mother's family. This study highlights the importance of a comprehensive understanding of various legal approaches in determining the status and rights of children born from premarital pregnancies. Keywords: Keywords: Dynamics; Islamic Law, Social Status, Pregnant Marriages Abstrak Penelitian ini bertujuan untuk menganalisis dinamika hukum Islam dan status sosial terkait keabsahan anak hasil kawin hamil dari berbagai pendekatan, termasuk pandangan Mazhab Syafi’i, Undang-Undang Perkawinan (UUP), dan Kompilasi Hukum Islam (KHI). Metode yang digunakan adalah kualitatif dengan pendekatan deskriptif-analitis, melalui studi literatur terhadap sumber-sumber hukum Islam klasik dan kontemporer, serta peraturan perundang-undangan Indonesia yang relevan. Analisis dilakukan untuk mengidentifikasi dan membandingkan pandangan berbagai otoritas hukum terhadap status hukum dan hak-hak anak yang lahir dari perkawinan wanita hamil. Hasil penelitian menunjukkan bahwa menurut Mazhab Syafi’i, anak yang lahir kurang dari enam bulan setelah perkawinan yang sah atau dimungkinkan adanya hubungan badan dianggap tidak sah dan tidak dinasabkan pada ayahnya, sehingga berdampak pada hak-hak anak. Namun, jika anak lahir lebih dari enam bulan setelah perkawinan yang sah, maka anak tersebut dianggap sah dan memiliki hak terhadap kedua orang tuanya. Menurut UUP dan KHI, anak yang lahir dari perkawinan wanita hamil akibat zina dianggap sah sepanjang lahir dari perkawinan yang sah, sehingga memiliki hak-hak yang wajib dipenuhi oleh kedua orang tuanya. Namun, jika anak lahir akibat zina di luar ikatan perkawinan yang sah, anak tersebut hanya mempunyai hubungan perdata dengan ibunya saja. Judicial review terhadap Pasal 43 (1) UUPA menghasilkan putusan bahwa anak yang dilahirkan di luar perkawinan juga memiliki hubungan perdata dengan ayah biologisnya dan keluarga ayahnya, selain dengan ibunya dan keluarga ibunya. Penelitian ini menyoroti pentingnya pemahaman yang komprehensif terhadap berbagai pendekatan hukum dalam menentukan status dan hak-hak anak hasil kawin hamil. Kata Kunci: Dinamika; Hukum Islam, Status Sosial, Kawin Hamil